Influence of multiple sleeve repairs on the structural integrity of gas pipelines - Otegui, Luis Jose (2002)
This paper addresses the structural integrity of gas pipelines with multiple full-encirclement weld repairs. The scope of the work is to identify and quantify the effects of the number and type of repairs, the distance between them, and the pressurization of the pipe to sleeve gap on the mechanical behaviour of the component. The study includes full-scale experimental testing and finite element modelling. Burst tests were carried out in tracts of pipelines removed from service, including various geometric configurations with and without circumferential girth welds. It is concluded that the reliability of the repairs is strongly influenced by the construction procedures and that interaction effects between successive repairs are not appreciable if the repairs are more than a half pipe diameter apart. © 2002 Elsevier Science Ltd. All rights reserved.